Returns to Schooling in Russia and Ukraine : A Semiparametric Approach to Cross-Country Comparative Analysis - Yuriy Gorodnichenko; Klara Sabirianova Peter (Institute for the Study of Labor (IZA), 2004)
This study provides the first set of estimates of the returns to schooling over an extended period in Russia and Ukraine (1985-2002). There has been an increase in returns to schooling in both countries but the increase is much bigger in Russia than in Ukraine. The intriguing question is why returns to schooling in Russia and Ukraine diverged so much over the transition period while the skill composition of employment did not. Our approach in analyzing the sources of cross-country differences in returns to schooling is to compare the Mincerian earnings functions between the two countries and then to employ decomposition techniques. Using semiparametric methods, we construct counterfactual wage distributions for university and secondary school graduates for Ukraine using the distributions of Russian characteristics, returns to characteristics, and unobservables. This allows us to decompose differences in returns to schooling between the two countries due to differences in the labor market returns (price effect), differences in unobservables (residual effect), and differences in the labor force composition (composition effect). We conclude that of these three effects the price effect makes a major contribution to the observed differences in the returns to schooling.
Keywords: C14; P50; O57; O15; J31; I20; 330; returns to schooling; earnings function; semiparametric approach; decomposition; counterfactual; cross-country analysis; retrospective data; Bildungsertrag; Übergangswirtschaft; Vergleich; Schätzung; Russland; Ukraine